School absenteeism and emotional deprivation: educational reality in upper class adolescents in Comalcalco, Tabasco - Arias De La Cruz, Antonia (2024)
The research aimed to reveal some of the psychoaffective-emotional aspects that students go through in their learning process and thus consider how emotional deprivation affects school absenteeism in a high economic context. In this research, an exploratory qualitative methodology has been used, since its object of study refers to subjective processes, adopting case studies as a resource. It has been based on an interpretive approach to the methodological instruments used. The data collection instruments used with adolescents who present emotional deprivation and educational lag have been in-depth interviews and the Person Learning Situation graphic device and in-depth interviews with selected informants. The main findings of this study highlight the close link between family problems and the educational processes of adolescents and demonstrate their negative impact not only on school activities but also on school absenteeism. The educational approach of this work not only describes the relationship between emotional deprivation and absenteeism in a general way, but also points out specific elements that can be considered to promote academic skills that encourage communication between parents and adolescents, which is crucial for improve your educational process.